Animal assisted therapy : CTAC method : techniques and exercises for dog assisted interventions - Ristol, Francesc, ....- (Miami : Smiles CTAC, 2015)
Over the course of all these years, our organization CTAC has proposed and put into practice myriad exercises for the world of animal assisted interventions. Each and every one of them has been documented, evaluated and employed by the various professionals with whom we've had the pleasure of sharing our work. All these exercises have contributed to achieving, by way of play, previously established objectives and, above all, have brought a smile to the faces of many individuals who our dogs have had the pleasure of working with. This book is intended as a guide for Animal Assisted Interventions professionals. In it, experts and technicians will find abundant ideas for creating new activities that enrich their work and help attain their therapeutic goals.